Fundamental and Applied Studies of Metal Ion Extraction by Crown Ethers into Imidazolium-Based Room Temperature Ionic Liquids - (:unkn) unknown (My University, 2012)
Growing recognition of the extraordinary physicochemical properties and unique solvation environment afforded by ionic liquids (ILs) has drawn increasing attention to these solvents as media for chemical separations. Until recently, little was known about how ionic liquids behave as solvents in this application, particularly in the extraction of ionic solutes such as metal ions. In contrast to the single pathway observed using molecular diluents (i.e., neutral complex extraction), metal ion extraction in these systems has been shown to proceed through as many as three competing pathways over a wide range of conditions. Despite this added complexity, the favorable physicochemical characteristics of the ionic liquids (e.g., non-flammability and unprecedented structural tunability), along with the higher extraction efficiencies and selectivities sometimes observed with these solvents, suggest that they offer significant potential in various separations applications on both the industrial and analytical scale. This potential will not be fully realized, however, without an improved understanding of the fundamental aspects of metal ion partitioning between ionic liquids and aqueous solutions. The objective of this work, therefore, is to clarify the factors controlling the balance among the various partitioning pathways observed when these solvents are employed in extraction. To this end, a series of N,N'-dialkylimidazolium-based ionic liquids have been evaluated as substitutes for the conventional organic solvents (i.e., n-alcohols) frequently employed in the extraction of alkali and alkaline earth cations from acidic aqueous phases by crown ethers. Insight into the fundamental aspects of metal ion extraction in these systems has been obtained by analysis of the acid and extractant dependencies of metal ion distribution ratios, measurements of the IL phase water content and of the solubility of the ionic liquids in the aqueous phase, determination of the partitioning of inorganic ions, and consideration of the relative hydrophobicities of the ionic liquids employed. To assess the potential practical utility of these ionic liquids as extraction solvents, these studies were aimed at obtaining information about the relationship between solvent structure and performance as solvents in the extraction of alkali and alkaline earth metal ions. The results obtained represent an important step in the development of guidelines for the rational design of ionic liquid-based metal ion separation systems.
Keywords: Crown Ether; Extraction; Hydrophobicity; Ionic Liquid; Metal Ion; Three-Path Model